Impact of climate change on the magnitude and extent of riverine floods in a Peruvian Andean–Amazonian basin - Saavedra, Danny (2026)
In the last two decades, approximately 2.15 million inhabitants in Peru were affected by floods, mainly concentrated in the Andean–Amazon basin, whose frequency has increased as a consequence of climate change. The objective of this research is to evaluate the potential impact of climate change on the magnitude of frequent (2-year) flood flows and the extent of flooded areas in the Huallaga River basin (HRB). We used the hydrological and hydrodynamic model MGB and an approach to select four CMIP6 global climate models (GCMs) representative of extreme conditions (Cold-dry, Cold-wet, Warm-dry, and Warm-wet) for the scenarios SSP2-4.5 and SSP5-8.5, analyzed in two future periods (2035–2065 and 2069–2099). The results show that the impacts on flood flows and flooded areas vary according to the selected GCM, with the largest increases concentrated in the headwater areas and along the main channel. Similarly, it was identified that the political provinces located in the north and the center-west of the HRB present the greatest agreement in the increase in flooded area (between 7 and 8 models of a total of 8 models). These findings are relevant for territorial planning, disaster risk management, and adaptation decision making in response to climate change.